PENGARUH FINANCIAL ATTITUDE, FINANCIAL BEHAVIOR DAN FINANCIAL KNOWLEDGE TERHADAP FINANCIAL DISTRESS PADA PEKERJA LAJANG DI KOTA PADANG - Defani Trilia Fitri; Armel Yentifa; Eka Siskawati (LP2M Politeknik Jambi, 2024)
This study aims to examine the influence of Financial attitude, Financial behavior, and Financial knowledge on Financial distress among single workers in Padang City. The sampling technique used in this study is purposive sampling, with a sample size of 400 respondents. Data collection was conducted using a questionnaire distributed through an online form (Google Forms), and instrument tests for validity and reliability were performed. The study method uses a quantitative approach, and data analysis techniques to test the hypotheses are conducted using SPSS software. The results of this study demonstrate that Financial attitude and Financial behavior affect Financial distress, whereas Financial knowledge does not affect Financial distress. This study also shows that Financial attitude, Financial behavior, and Financial knowledge simultaneously influence Financial distress.